Exercise in Adolescent Idiopathic Scoliosis: A Narrative Review - Yulianti Tjahyadi; Ellyana Sungkar (Indonesian Journal Publisher, 2026)
Background: Adolescent Idiopathic Scoliosis (AIS) is a three-dimensional spinal deformity that emerges during adolescence and has the potential to progress during the growth period, thereby affecting neuromusculoskeletal function, postural balance, and the patient’s quality of life. Objective: This study aims to review the role of exercise in the conservative management of AIS in controlling curve progression, improving postural control, and enhancing patient function and quality of life. Methods: This study used a narrative literature review design by examining various relevant scientific literatures regarding exercise interventions in AIS. Literature searches were conducted through the PubMed, Scopus, and Google Scholar databases using related keywords such as “adolescent idiopathic scoliosis,” “scoliosis exercise,” “physiotherapeutic scoliosis-specific exercises,” “Schroth method,” and “SEAS.” Included articles consisted of original research, systematic reviews, meta-analyses, and clinical guidelines discussing exercise as part of the conservative management of AIS. The selected literature was then analyzed descriptively to identify the exercise approaches used and their clinical implications. Results: The review results show that exercises based on Physiotherapeutic Scoliosis-Specific Exercises (PSSE), such as the Schroth method and the Scientific Exercise Approach to Scoliosis (SEAS), play a role in improving three-dimensional spinal correction, enhancing neuromuscular control, improving postural balance, and helping to inhibit curve progression. Exercises such as core muscle strengthening and aerobic exercise contribute to improving trunk stability and the functional capacity of patients. Conclusion: Exercise is a component of the conservative management of AIS and has the potential to improve clinical outcomes and patients’ quality of life. Therefore, evidence-based and individually tailored exercise programs are highly recommended in rehabilitation practice to maximize the effectiveness of conservative therapy in AIS.